Evaluation of multiple‐alternative prompts during tact training. Issue 2 (21st January 2016) - Leaf, Justin B.; Townley‐Cochran, Donna; Mitchell, Erin; Milne, Christine; Alcalay, Aditt; Leaf, Jeremy; Leaf, Ron; Taubman, Mitch; McEachin, John; Oppenheim‐Leaf, Misty L.
Abstract : This study compared 2 methods of fading prompts while teaching tacts to 3 individuals who had been diagnosed with autism spectrum disorder (ASD). The 1st method involved use of an echoic prompt and prompt fading. The 2nd method involved providing multiple‐alternative answers and fading by increasing the difficulty of the discrimination. An adapted alternating‐treatments design showed that both procedures were more effective than a no‐intervention control condition. Providing multiple alternatives did not increase error rates or teaching time, and better maintenance was shown for tacts taught with the multiple‐alternative prompt.